Visual Images Associated With Reporting about Biodegradables in Nigerian Newspapers - Ben-Collins Emeka NDINOJUO (International Journal of Environmental, Sustainability, and Social Science, 2020)
Concern for the environment has become a global movement among countries of the world with pollution at the center. One of the solutions advocated towards improving solid waste management is the use of biodegradables. Therefore, the aim of this paper was to analyze the images associated with reporting biodegradables in five daily Nigerian newspapers, The Cable, The Guardian, Leadership, Premium Times and The Punch from April 1, 2019 to August 30, 2019. The study drew its theoretical foundation on the theory of Multimodal Discourse Analysis using quantitative and qualitative content analysis. Findings revealed 12 articles with 10 containing images. Four themes were associated with the images; environmental pollution (5), plastic products (1), politicians/political (3), and logo theme (1). Embedded meanings were uncovered within the images. Recommendations include allocating more resources towards training of environmental reporters to increase the output and quality of reports about the environment and biodegradables in particular.